Live imaging of active fluorophore labelled Wnt proteins - Holzer, Tatjana; Trageser, Benjamin; Özbek, Suat (FEBS letters, 2012)
Here, we have generated a Wnt2b-EGFP fusion protein that retains functionality in bona fide Wnt activity assays, although the secreted protein is rapidly cleaved by extracellular proteases. We can show with this new tool that Wnt2b-EGFP moves along the microtubules of Wnt producing cells and that this directed movement is essential for the secretion of active Wnt protein.